Rekomendasi Penentuan Desa Terbaik dengan Kombinasi Metode OWA (Ordered Weighted Avarage) dan Metode SAW (Simple Additive Weighting) berbasis Web - Simangunsong, Agustina; Hamdani, Rita (LPPM UNIKA Santo Thomas Medan, 2020)
The success of the government is determined by essential aspects of the village and has increased every day and has changed into a town that has independence in carrying out activities and survival by each of its residents, to support and improve the quality of government villages which motivate for villages to compete to become the best village through a series of costs to improve the quality of the town. The process of determining the best village starts from the sub-district. The winner will be smart at the city district level up to the national level, in the process of determining the best town according to government regulations in sending villages with five aspects and each aspect that has specified specifications and through validation from the government In the process of the government in the form of a committee conducting visits and conducting assessments based on the completeness of the data with the team for each aspect and giving to the committee based on individual orders, the value submitted will do the calculation by determining the final cost of the process of finding an average value -average overall and do the division of the total aspects. To assist the procedure in choosing the best village, the researcher wants to develop an online decision support system application with features that will be equipped in the developed application by uploading documents according to conditions in the field and documentation carried out by the team towards the village, so that the order process is open. It can be witnessed by all concerned, while in the Calculation and analysis Process using the OWA (ORDERED WEIGHTED AVERAGE) combination operator to determine the average value calculation and the SAW (Simple Additive Weighting) Method as part of the ranking of several existing villages